ANALYSIS OF EMPLOYEE WELL-BEING AND WORK ENGAGEMENT ON TURNOVER INTENTION ON HEALTH PERSONNEL AT PKU MUHAMMADIYAH HOSPITAL SRUWENG - Rheni Haryanti (International Journal Labs, 2022)
Employee well-being has an important role that will increase effectiveness and efficiency so as to increase work engagement which has a positive impact on improving services for patients in hospitals. The high workload that is not in accordance with the welfare of health workers in hospitals will have an impact on the desire of health workers to leave the hospital where they currently work (turnover intention). The purpose of this study was to analyze employee well-being and work engagement on turnover intention in health workers at PKU Muhammadiyah Sruweng Hospital. The type of research conducted is descriptive qualitative research. The research sample specified in this study was 20 health workers. Researchers collected data by in-depth interview method assisted by open-answer questions from respondents with predetermined interview guides. The results showed that employee well-being in health workers was in the high category. Work engagement on health is in the medium category. Meanwhile, the turnover intention of health workers at PKU Muhamamdiyah Hospital Sruweng is high.